FLEXURAL TESTING OF WOOD-CONCRETE COMPOSITE BEAM MADE FROM KAMPER AND BANGKIRAI WOOD - Yoresta, Fengky Satria (LANGKAU BETANG: JURNAL ARSITEKTUR, 2015)
Certain wood has a tensile strength that almost equal with steel rebar in reinforced concrete beams. This research aims to understand the capacity and flexural behavior of concrete beams reinforced by wood (wood-concrete composite beam). Two different types of beams based on placement positions of wood layers are proposed in this study. Two kinds of wood used are consisted of Bangkirai (Shorea laevifolia) and Kamper (Cinnamomum camphora), meanwhile the concrete mix ratio for all beams is 1 cement : 2 fine aggregates : 3 coarse aggregates. Bending test is conducted by using one-point loading method. The results show that composite beam using Bangkirai wood is stronger than beams using Kamper wood. More thicker wood layer in tensile area will increase the flexural strength of beams. Crack patterns identified could be classified into flexural cracks, shear cracks, and split on wood layerÂ Beberapa jenis kayu tertentu memiliki kekuatan tarik yang hampir sama dengan tulangan baja pada balok beton bertulang. Penelitian ini bertujuan memahami kapasitas dan perilaku lentur balok beton bertulang yang diperkuat menggunakan kayu (balok komposit beton-kayu). Dua tipe balok yang berbeda berdasarkan posisi penempatan kayu digunakan dalam penelitian ini. Dua jenis kayu yang digunakan adalah kayu Bangkirai (Shorea laevifolia) and Kamper (Cinnamomum camphora), sementara itu rasio campuran beton untuk semua balok menggunakan perbandingan 1 semen : 2 agregat halus : 3 agregat kasar. Pengujian lentur dilakukan menggunakan metode one-point loading. Hasil penelitian menunjukkan bahwa balok komposit dengan kayu Bangkirai lebih kuat dibandingkan balok dengan kayu Kamper. Semakin tebal lapisan kayu yang berada di daerah tarik akan meningkatkan kekuatan lentur balok. Pola kerusakan yang teridentifikasi dapat diklasifikasikan menjadi retak lentur, retak geser, dan pecah pada kayuREFERENCESBoen T. (2010). Retrofitting Simple Buildings Damaged by Earthquakes. World Seismic Safety Initiative. Indonesia.Chauf KA. (2005). Karakteristik Mekanik Kayu Kamper sebagai Bahan Konstruksi. Majalah Ilmiah MEKTEK 7: 41-47.Gangarao HVS, Narendra T & Vijay PV. (2007). Reinforced Concrete Design with FRP Composites. CRC Press, Boca Raton.PKKI (Indonesian Timber Construction Code). (1961). PKKI NI â€“ 5 1961. Direktorat Jenderal Cipta Karya Departemen Pekerjaan Umum, Bandung.Pranata YA, Bambang S & Johannes AT. (2012). Rasio Modulus Penampang Elastik Balok Kayu Laminasi-Baut. Jurnal Teknik Sipil 19: 223-236.Thelandersson S. (2003). Introduction: Wood as a construction material. Pp 15-22 in Sven T & Hans JL (Eds) Timber Engineering. John Wiley & Sons Ltd, West Sussex.